2022
DOI: 10.1093/jac/dkac288
|View full text |Cite
|
Sign up to set email alerts
|

Blood and intra-abdominal Candida spp. from a multicentre study conducted in Madrid using EUCAST: emergence of fluconazole resistance in Candida parapsilosis, low echinocandin resistance and absence of Candida auris

Abstract: Objectives We prospectively monitored the epidemiology and antifungal susceptibility of Candida spp. from blood cultures and intra-abdominal samples in patients admitted to hospitals in the Madrid area. Methods Between 2019 and 2021, we prospectively collected incident isolates [one per species, patient and compartment (blood cultures versus intra-abdominal samples)] from patients admitted to any of 16 hospitals located in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Although the agreement between the commercial and reference methods for Candida species susceptibility has been described as variable, since it may depend on the antifungals, the species, and the incubation time [ 22 , 23 , 24 , 25 ], our results provided relevant indications. In fact, the remarkable resistance rates to: 1) fluconazole in C. parapsilosis complex (up to 31.2%), C. glabrata (up to 13.5%), and C. guilliermondii (up to 33.3%); 2) EUCAST voriconazole in C. parapsilosis complex (up to 11%); 3) EUCAST and/or CLSI echinocandin in C. tropicalis (up to 12.5%), C. krusei (up to 25%), and C. guilliermondii (up to 33.3%) were consistent with those of both the ARIA project and recent reports analyzing clinical samples from Greece and the Madrid region that highlighted the emergence of fluconazole resistance in C. parapsilosis complex (up to 23%) and a low rate of resistance to echinocandins (up to 1–3%) [ 7 , 15 ]. Our results went into further detail by also highlighting an increase in resistance to fluconazole in C. albicans (up to 4.5%), and fluconazole (up to 24.5%) and echinocandin (up to 5.1%) in C. parapsilosis complex, respectively, despite the reduced frequency of C. parapsilosis complex in 2021.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although the agreement between the commercial and reference methods for Candida species susceptibility has been described as variable, since it may depend on the antifungals, the species, and the incubation time [ 22 , 23 , 24 , 25 ], our results provided relevant indications. In fact, the remarkable resistance rates to: 1) fluconazole in C. parapsilosis complex (up to 31.2%), C. glabrata (up to 13.5%), and C. guilliermondii (up to 33.3%); 2) EUCAST voriconazole in C. parapsilosis complex (up to 11%); 3) EUCAST and/or CLSI echinocandin in C. tropicalis (up to 12.5%), C. krusei (up to 25%), and C. guilliermondii (up to 33.3%) were consistent with those of both the ARIA project and recent reports analyzing clinical samples from Greece and the Madrid region that highlighted the emergence of fluconazole resistance in C. parapsilosis complex (up to 23%) and a low rate of resistance to echinocandins (up to 1–3%) [ 7 , 15 ]. Our results went into further detail by also highlighting an increase in resistance to fluconazole in C. albicans (up to 4.5%), and fluconazole (up to 24.5%) and echinocandin (up to 5.1%) in C. parapsilosis complex, respectively, despite the reduced frequency of C. parapsilosis complex in 2021.…”
Section: Discussionsupporting
confidence: 84%
“…Candidemia is one of the most frequent health care-associated bloodstream infections (BSIs) and represents a global clinical challenge, especially given the burden of associated morbidity and mortality [ 1 , 2 ]. Several authors have reported an increase in the incidence of Candida species BSIs during the SARS-CoV-2 pandemic, highlighting the need for active surveillance especially in patients with severe COVID-19 [ 3 , 4 , 5 , 6 , 7 ]. Antibiotic therapy, corticosteroids, immunosuppressive therapy, intravascular devices, long hospital stays, and direct disruption of the intestinal barrier caused by SARS-CoV-2 have been deemed to pave the way to Candida species BSIs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach becomes particularly pertinent in light of the increasing prevalence of Candida glabrata , Candida parapsilosis and multiresistant Candida auris 6,16 . And this concern becomes even more pronounced when transitioning from newer antifungal agents like echinocandins to oral alternatives such as fluconazole in which the emergence of drug resistance is a more obvious phenomenon 7,8,28 . A well‐considered approach to adequate antifungal selection 29 is crucial to forestall the potential development of resistant strains, especially in the context of fluconazole usage, which has already been associated with the emergence of multiresistant species.…”
Section: Exploring the Ideal Treatment Durationmentioning
confidence: 99%
“…8 Isolates harbouring the G458S substitution were recently detected in a hospital located in Madrid in late 2021. [9][10][11] Phenotypic FRCP was detected for the first time in April 2021, in patients admitted to a referral hospital in Burgos, a city located in Northern Spain. We here report the spread of such isolates across the hospital and describe a new outbreak caused by FCRP isolates in a hospital in Spain.…”
Section: Introductionmentioning
confidence: 99%